Gentry and common folk : political culture on a Virginia frontier, 1740-1789 - Tillson, Albert H., 1948- (University Press of Kentucky, 1991)
In the late eighteenth century, the Upper Valley of Virginia experienced a conflict between the elitist culture of the gentry and the more republican values of the populace. Albert Tillson addresses here several major issues in historical scholarship on Virginia and the southern backcountry, focusing on changing political values in the late colonial and Revolutionary eras. In the colonial period, Tillson shows, the Upper Valley's deferential culture was much less pervasive than has often been suggested. Although the gentry maintained elitist values in the county courts and some other political.